2003
DOI: 10.1038/sj.onc.1207340
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin M suppresses the malignant phenotype of human MDA-MB-435S cells

Abstract: Proteases are involved in many aspects of tumor progression, including cell survival and proliferation, escape from immune surveillance, cell adhesion and migration, remodeling and invasion of the extracellular matrix. Several lysosomal cysteine proteases have been cloned and shown to be overexpressed in cancer; yet, despite the great potential for development of novel therapeutics, we still know little about the regulation of their proteolytic activity. Cystatins such as cystatin M are potent endogenous prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 61 publications
2
78
0
1
Order By: Relevance
“…The role of CST6 as a tumor suppressor is well established in many cancer types including breast (63)(64)(65)(66)(67) and prostate cancer (68). CST6 is a potent endogenous protein inhibitor of lysosomal proteases and its down-regulation, mainly through epigenetic inactivation, promotes tumor cell invasion, cell proliferation and matrix remodeling (64,67). Increased expression of KRT9, KRT10, FLG and FLG2, which are involved in terminal epidermal differentiation, was reported in cSCC using gene-expression analysis (69).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CST6 as a tumor suppressor is well established in many cancer types including breast (63)(64)(65)(66)(67) and prostate cancer (68). CST6 is a potent endogenous protein inhibitor of lysosomal proteases and its down-regulation, mainly through epigenetic inactivation, promotes tumor cell invasion, cell proliferation and matrix remodeling (64,67). Increased expression of KRT9, KRT10, FLG and FLG2, which are involved in terminal epidermal differentiation, was reported in cSCC using gene-expression analysis (69).…”
Section: Discussionmentioning
confidence: 99%
“…When exogenously expressed in human MDA-MB-435S breast cancer cells, CST6 significantly alters the neoplastic phenotype in vitro, resulting in diminished cell proliferation, loss of cell migration, inhibition of Matrigel invasion, and reduced endothelial cell adhesion (Shridhar et al, 2004). Furthermore, expression of CST6 in MDA-MB-435S breast cancer cells delays tumorigenesis by transplanted cells and suppresses spontaneous formation of liver and lung metastases (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of CST6 in MDA-MB-435S breast cancer cells delays tumorigenesis by transplanted cells and suppresses spontaneous formation of liver and lung metastases (Zhang et al, 2004). More recently, it has been shown that CST6 is epigenetically regulated by DNA methylation-dependent silencing in breast cancer cell lines (Ai et al, 2006;Rivenbark et al, 2006a;Schagdarsurengin et al, 2006;Shridhar et al, 2004) and primary invasive ductal carcinomas (Ai et al, 2006;Schagdarsurengin et al, 2006). Ai et al showed that 12/20 (60%) primary breast tumors exhibit CST6 promoter hypermethylation, and microdissection of individual cells from select tumors revealed that methylation occurs in both DCIS and IDC cells (Ai et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wound healing, cystatin M expression was not found in the edge of migrating keratinocytes and in epidermal neoplasia cystatin M was only detected in differentiated cells and keratinized cell nests (Zeeuwen et al, 2002). Cystatin M downregulation was also observed in different cancer cells, including prostate cancer, colon cancer, glioblastoma, lung cancer and melanoma Shridhar et al, 2004). This indicates that cystatin M may be epigenetically downregulated in other cancers.…”
Section: Discussionmentioning
confidence: 99%